Does variation in residents' spatial mobility affect their preferences concerning local governance?. (August 2019) - Wicki, Michael; Guidon, Sergio; Bernauer, Thomas; Axhausen, Kay
Abstract: The geographic scope of people's mobility behaviour has generally increased over recent decades. Yet, many policies continue to be enacted and implemented at the local level (e.g. in municipalities), leading to a mismatch in geographical scope. Our research thus speaks to the debate on how residents' increased spatial mobility has prompted a disjunction between residents' preferences in terms of governance and how governance is organized in reality. This conjectures that residents with a larger mobility space are more likely to prefer local governance reforms creating larger units for the sake of greater efficiency. In this study, we examine how variation in spatial mobility, mediated by place attachment, affects residents' preferences concerning municipal reforms, in particular upscaling of jurisdictional territories. Moreover, we assess these claims with an empirical focus on Switzerland, a particularly interesting case due to its strong tradition of political decentralization and local governance. The analysis is based on data from a two-stage survey with a representative sample of 1506 adult residents from the Canton of Zurich, the most populous Swiss subnational unit. We measured individuals' spatial mobility by calculating the individual social (network) geography for each of the study participants and examined how it relates to preferences concerning municipal reforms. Altogether, our results provide support for a negative correlation between service satisfaction and spatial mobility, but a positive correlation between spatial mobility and municipal attachment. Contrary to our theoretical expectations, larger social network geographies do not lead to more support for municipal reforms. Highlights: Measurement of individuals' spatial mobility by calculating the individual social (network) geography of 1506 adult residents. Higher spatial mobility correlated with higher municipal attachment. Larger social network geographies do not lead to more support for municipal reforms. Larger social network geographies even decrease support for municipal reforms that would merge tasks.